Long-term Safety and Efficacy of Mexiletine in Myotonic Dystrophy Types 1 and 2. Issue 5 (October 2021) - Mousele, Christina; Matthews, Emma; Pitceathly, Robert D.S.; Hanna, Michael G.; MacDonald, Susan; Savvatis, Konstantinos; Carr, Aisling; Turner, Christopher
Abstract : Background and Objective: Myotonic dystrophy types 1 and 2 are progressive multisystem genetic disorders whose core clinical feature is myotonia. Mexiletine, an antagonist of voltage-gated sodium channels, is a recommended antimyotonic agent in the nondystrophic myotonias, but its use in myotonic dystrophy is limited because of lack of data regarding its long-term efficacy and safety profile. Methods: To address this issue, this study retrospectively evaluated patients with myotonic dystrophy receiving mexiletine over a mean time period of 32.9 months (range 0.1–216 months). Results: This study demonstrated that 96% of patients reported some improvement in myotonia symptoms with mexiletine treatment. No clinically relevant cardiac adverse events were associated with the long-term use of mexiletine. Conclusions: These findings support that mexiletine is both safe and effective when used long-term in myotonic dystrophy. Classification of Evidence: This study provides Class IV evidence that mexiletine is a well-tolerated and effective treatment for myotonic dystrophy types 1 and 2.